PERIODONTAL STATUS IN INDIVIDUALS WITH MEDITERRANEAN DIET (LITERATURE REVIEW) - Astuti, Luki; Aurelia, Sania; Komala, Olivia Nauli (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2023)
Introduction: The condition of the periodontal tissues can usually be checked by conducting a periodontal screening or examination of the periodontal tissues. From this examination, the health status of the periodontal tissue will be obtained, which can facilitate findings related to periodontal disease. Diet has been reported to be significantly associated with periodontal health. A diet that is known to have a beneficial effect on treating inflammation in the oral cavity is the Mediterranean diet. Aim: This literature review discusses the conclusive results of periodontal status in patients or individuals with a Mediterranean diet obtained from several studies. Review: The clinical parameters measured on examination of the periodontal tissue to obtain periodontal health status were plaque and calculus scores, bleeding on probing (BOP), probing pocket depth (PPD), gingival recession (GR), and clinical attachment level or clinical attachment loss (CAL). Nutritional factors are known to act as sources of interference and modulation. A diet that lacks micronutrients (vitamins and minerals) can exacerbate the inflammatory response of the periodontal tissues. The Mediterranean diet is known to be low in saturated fat and rich in polyphenols, oleocanthal, lycopene, minerals, fiber, vitamins, and omega-3 fatty acids. This diet can provide antioxidant and anti-inflammatory effects that can affect the periodontal tissue. Although not very numerous, there are studies examining periodontal tissue and periodontal disease in individuals with a Mediterranean diet. These studies require the health status of the periodontal tissues. Conclusion: Periodontal health status in individuals with a Mediterranean diet based on several studies shows quite good results, where there is a decrease in scores on bleeding on probing (BOP), pocket depth (PD), clinical attachment loss (CAL), and low plaque index.